THE STRATEGIES USED BY ENGLISH TEACHERS IN TEACHING READING COMPREHENSION OF JUNIOR HIGH SCHOOLS IN RAYON 2 PELALAWAN - Ratni Atika; Erni Erni; Jismulatif Jismulatif (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is aimed at investigating the strategies in teaching reading comprehension used by English teachers of junior high schools in Rayon 2 Pelalawan Regency. Using total sampling, 63 teachers employed in this study were taken as the sample of this research. This study employed mixed method, combining quantitative and qualitative methods of data collection. The quantitative data were collected from a questionnaire while the qualitative ones were obtained through semistructured interviews. The questionnaire consists of three categories; Matacognitive strategy instruction (planning, monitoring, and evaluating), Cognitive strategy instruction (visualization, and summarizing) and Social strategy instruction (Cooperative learning and asking questions). The interview was deliberately chosen for the researcher intended to understand the depth of the data. The findings of this study revealed that the teacher tent to use Metacognitive strategy instruction, Cognitive strategy instruction, and Social strategy instruction in teaching reading comprehension. This result showed that the most strategies used by 60 (95%) of teachers in Metacognitive strategy instruction is monitoring (96,3%), summarizing as Cognitive strategy instruction (84,7%) and asking questions as Social strategy instruction (86%). The lowest point of the strategy is evaluating (54%). There were also additional respondents through an interview that mostly used Metacognitive Strategy Instruction and Social Strategy Instruction. Meanwhile, since COVID-19, between teachers and students need to take online learning, using media online platforms such as google classroom, whatsapp, and youtube. Furthermore, an occurrence of some problems during the teaching-learning process was inevitable. Among some other problems, students’ extreme diversity, lack of facilities, lack of students’ motivation, and bad networks for online learning in reading activity.Key Words: Reading Comprehension, Teaching Strategy, Pelalawan Regency